Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Gendered care work and environmental injustice: A feminist analysis of educator's emotional labor in disaster recovery - Shtob, Daniel A.; Petrucci, Larissa (Environmental Justice, 2021)
Although environmental justice researchers have long been interested in the connections between disaster recovery, gender, and home- and community-based care, the consequences of the post-disaster performance of emotional labor by workers in care occupations have largely gone unnoticed. To address this gap in the environmental injustice literature, in this exploratory article we employ a feminist analysis of firsthand accounts of elementary educators' professional and personal experiences caring for their students in the Florida Keys after Hurricane Irma. We find that caring labor was increasingly necessary in the post-disaster context, both inside and outside the classroom. Teachers and other care professionals in feminized occupations may, therefore, perform an emotional double duty, supporting their students' emotional needs while also contending—as working- and middle-class individuals—with the personal consequences of disaster. We suggest that these educators may bear an unrecognized and undercompensated disproportionate burden at the intersection of class and occupational status. Because of this, we introduce an underexplored component to the racialized disaster patriarchy and intersectional disaster research: feminized occupational status. Inspired by environmental justice research legacies developed in the wake of earlier Gulf Coast disasters, we draw attention to the contributions of these absolutely essential recovery workers and how they may experience environmental injustice even as they contribute to others' recovery. Our goals are to promote recognition and fair distribution of burdens, encourage research into the contours of environmental justice and care work, and support the development of more just planning, training, and compensation regimes.
Keywords: amériques; approches et analyses; care; discipline; floride; intersectionnalité; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; émotions

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge philosophy companions, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."--The publisher.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Genre, migrations et globalisation de la reproduction sociale - Verschuur, Christine; (Dir), Christine Catarino; Par, Dirigé. (L'Harmattan, 2013)
Les études féministes ont souligné l’importance d’étudier le travail auparavant invisible des femmes, productif et reproductif, et la nouvelle division du travail productif et reproductif dans la mondialisation du capitalisme. L’analyse du capitalisme mondialisé dans une perspective décoloniale permet de comprendre qu’il n’est pas seulement un système économique ni seulement un système culturel mais un réseau global de pouvoir intégré par des processus économiques, politiques et culturels qui constituent un ensemble. Partout on observe un système, social, économique, culturel, moral d’organisation de la reproduction sociale, y compris le care, entendu comme échange économico-affectif, qui implique des biens et des services liés à l’économie capitaliste. Dans le nouvel ordre économique global, que l’on pourrait toujours qualifier de colonial, caractérisé par la nouvelle division internationale du travail, l’articulation entre rapports sociaux dans l’économie domestique et capitaliste prend de nouvelles formes. Mais le système repose toujours sur l’organisation de l’ensemble des activités et des rapports indispensables à la reproduction sociale, par-delà les frontières, dans des réseaux et foyers transnationaux, en s’appuyant sur des discours de genre et de race, voire de classe. Dans ce système, les femmes migrantes sont particulièrement présentes. Elles constituent un maillon essentiel du système de protection sociale aux Nords, y contribuent à la production de richesses, tout en assurant l’organisation de la reproduction sociale aux Suds, dans les foyers qu’elles ont gardés dans leurs pays d’origine.
Keywords: approches et analyses; capitalisme; care; cours; discipline; féminisme décolonial; globalisation; intersectionnalité; justice sociale; militance; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences humaines; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; travail; travail du sexe

Les rabat-joie féministes (et autres sujets obstinés) - Ahmed, Sara (Cahiers du Genre, 2012)
Interrogeant la figure de la « féministe rabat-joie », cet article propose d’en explorer la négativité, aussi bien que la capacité d’agir dont elle est la promesse. Il s’agit ainsi, en repositionnant la pensée féministe comme critique de l’injonction au bonheur, de comprendre le sujet féministe en tant que sujet obstiné. L’obstination féministe est alors appréhendée comme le socle incertain d’une politique collective traduisant les émotions individuelles, la douleur ou la colère ressentie face aux injustices. Au-delà, la figure du sujet obstiné permet de saisir la façon dont, au sein des espaces féministes, les femmes noires ont pu être réduites à leur colère et désignées comme cause des divisions engendrées par le racisme. La position de sujet obstiné constituerait ainsi autant un lieu de tensions que de revendications politiques. https://www.saranahmed.com/
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; care; cours; discipline; europe; fem1000; féminismes noirs; incontournable; intersectionnalité; luttes; militance; occident; orient; philosophie; phénoménologie; politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Évaluation des besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale - Larochelle, Émilie (2010)
Les femmes handicapées constituent un groupe de la population particulièrement vulnérable à la violence conjugale. En effet, elles risqueraient davantage que les autres femmes d’être victimes de violence de la part de leur conjoint et subiraient des formes plus sévères de violence (Brownridge 2006). Elles rapporteraient également de plus longues périodes d’abus (Nosek et autres 2001a). Pourtant, peu de ressources spécialisées en matière de violence conjugale leur sont accessibles, et les études sur l’accessibilité de ces ressources ainsi que sur la violence conjugale à l’égard des femmes handicapées se font rares. C’est dans ce contexte que l’Office des personnes handicapées du Québec (l’Office) et le ministère de la Santé et des Services sociaux (MSSS) se sont engagés à documenter la problématique de la violence conjugale envers les femmes handicapées dans le cadre du Plan d’action gouvernemental 2004-2009 en matière de violence conjugale (Québec 2004). Afin de remplir cet engagement, l’Office, en partenariat avec le MSSS, a entrepris en avril 2008 le projet intitulé Évaluation des besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale. Ce projet vise à : 1. Documenter la problématique de la violence conjugale envers les femmes handicapées. 2. Évaluer les besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale par le réseau de la santé et des services sociaux et les maisons d’hébergement. 3. Formuler des recommandations visant la prévention de la violence conjugale auprès des femmes handicapées ainsi que l’adaptation des services aux réalités particulières vécues par celles-ci. Ce projet d’évaluation, par ses résultats et ses recommandations, contribue également à répondre à l’une des priorités d’intervention de la politique gouvernementale À part entière : pour un véritable exercice du droit à l’égalité, soit agir contre toute forme d’exploitation, de violence et de maltraitance (Québec 2009 : 31). Rappelons que cette politique a été adoptée le 4 juin 2009 par le gouvernement du Québec et a pour but d’accroître, sur une période de dix ans, la participation sociale des personnes handicapées.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; amériques; approches et analyses; canada; care; cours; discipline; intersectionnalité; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; thématiques; travail social

L’impact des violences structurelle et conjugale en contexte migratoire: Perceptions d’intervenants pour le contrer - Rojas-Viger, Celia (Nouvelles pratiques sociales, 2008)
Résumé Le Canada et le Québec, sociétés pluriethniques, possèdent des politiques et des programmes de promotion et de prévention pour contrer les violences faites aux femmes, mais reconnaissent que le défi est de taille dans le contexte migratoire. Les immigrantes, confrontées à la violence conjugale, ne disposent souvent pas d’accessibilité culturelle aux services sociaux et de santé ou n’obtiennent pas de réponse adéquate à leurs besoins. Toutefois, certains organismes ont des projets pour leur venir en aide mais ils ne sont pas systématiques. L’article présente les résultats d’une recherche exploratoire, avec approche ethnologique, qui documente la perception de 10 intervenants d’organismes communautaires et institutionnels concernant leurs activités dans le domaine et leur préoccupation pour la promotion et la prévention primaire, même si leurs pratiques concrètes sont surtout centrées sur la prévention secondaire. Maints empêchements les limitent, mais leurs perceptions des réponses promotionnelles et préventives mettent en lumière l’impact de la violence structurelle et de la violence conjugale et orientent les perspectives de renouvellement des pratiques d’intervention sociosanitaire en matière de violence conjugale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; care; cours; discipline; histoire et politique; intersectionnalité; inégalités; justice sociale; migration; médecine; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; systèmes d'oppressions; thématiques; trs3500; violence systémique; violences; violences conjugales

Les tactiques féministes confrontées aux « tirs amis » dans le mouvement des femmes en Irlande - Taylor, Judith (Politix, 2007)
Cet article examine les modèles courants d’intelligibilité de l’interaction tactique entre les acteurs des mouvements sociaux et montre leur insuffisance pour rendre compte de l’invention tactique dont a dû faire preuve le mouvement des femmes en Irlande. Une analyse des efforts déployés par les féministes irlandaises pour l’extension du droit à l’avortement met en question l’idée que les innovations tactiques ne répondraient qu’aux contre-mouvements ou à la répression de l’État. L’expression « tir ami » fait référence au processus par lequel des groupes qui ne sont pas en opposition avec un mouvement, mais qui n’en font pas non plus partie, constituent une menace pour les finalités de ce mouvement. L’observation de la campagne féministe, de ses meetings et de l’ensemble de sa mise en scène politique donne des aperçus significatifs sur les effets des tirs amis et, spécifiquement, sur le rôle des hommes dans les mouvements de femmes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; avortement; care; corps; cours; discipline; droits des femmes*; europe; intersectionnalité; irlande; justice reproductive; justice sociale; pol5185; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques

Vers une analyse alternative de la mondialisation: les circuits de survie et leurs acteurs - Sassen, Saskia (Cahiers du Genre, 2006)
De nombreuses femmes migrent dans le cadre de la mondialisation : elles partent pour s’occuper du service domestique, garder des d’enfants, devenir infirmières, ou exercer la prostitution; elles utilisent aussi la filière de mariages arrangés. Cette migration est le résultat de conditions ou de dynamiques très diverses dont on peut se demander si elles sont en rupture ou en continuité avec les anciennes histoires bien répertoriées de migration et d’exploitation. Il faut se situer à deux niveaux : d’un côté, les activités souvent traditionnelles, qu’elles soient liées à la survie ou à la recherche de profits, se mondialisent et contribuent aujourd’hui à la création, à l’échelle mondiale, d’une masse de travailleuses mal rémunérées. D’un autre côté, les pays du Nord voient dans l’apport croissant de femmes migrantes un élément leur permettant de réorganiser profondément le monde du travail. Ce genre de dynamique est particulièrement visible dans les villes mondialisées, qui constituent aussi des pôles d’attraction pour le capital multinational. Que ce soit au niveau de la ville ou à celui des circuits de survie, les femmes deviennent des actrices incontournables des nouveaux types d’économie en expansion. On leur attribue une moindre valeur économique et pourtant elles constituent des éléments clés dans la construction des économies nouvelles.
Keywords: 2000 à aujourd'hui; approches et analyses; care; cours; discipline; histoire et politique; intersectionnalité; inégalités; justice sociale; migration; pol4022; premier cycle; périodes historiques; ressource en ligne; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis

Toward a Feminist Theory of Disability - Wendell, Susan (Hypatia, 1989)
We need a feminist theory of disability, both because 16 percent of women are disabled, and because the oppression of disabled people is closely linked to the cultural oppression of the body. Disability is not a biological given; like gender, it is socially constructed from biologically reality. Our culture idealizes the body and demands that we control it. Thus, although most people will be disabled at some time in their lives, the disabled are made "the other," who symbolize failure of control and the threat of pain, limitation, dependency, and death. If disabled people and their knowledge were fully integrated into society, everyone's relation to her/his real body would be liberated.
Keywords: 1900-1999; 1980-1989; EDI; approches et analyses; bioéthique; care; corps; cours; discipline; intersectionnalité; philosophie; premier cycle; périodes historiques; ressource en ligne; santé; sciences humaines; sex1911; sex1920; thématiques; éthique; études critiques du handicap